{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Stitz-Zeager_College_Algebra_e-book

# Finally we get t 12 this means it will 5 take 12

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: (x2 − 4x + 13) = (3x − 1)(x − (2 + 3i))(x − (2 − 3i)) 1 Zeros: x = , x = 2 ± 3i 3 √ √ 4 + 9x2 + 20 = x2 + 4 x2 + 5 = (x − 2i)(x + 2i) x − i 5 x + i 5 (e) x √ Zeros: x = ±2i, ±i 5 √ √ 2 12 (f) 4x4 − 4x3 + 13x2 − 12x + 3 = x − 2 4x2 + 12 = 4 x − 1 (x + i 3)(x − i 3) 2 √ 1 Zeros: x = , x = ± 3i 2 3 + 3x2 + 4x + 12 = (x + 3) x2 + 4 = (x + 3)(x + 2i)(x − 2i) (g) x Zeros: x = −3, ±2i (h) 2x4 − 7x3 + 14x2 − 15x + 6 = (x − 1)2 2x2 − 3x + 6 √ √ 3 39 3 39 2 x− = 2(x − 1) + i x− − i 4 4 4 4 √ 3 39 Zeros: x = 1, x = ± i 4 4 3.4 Complex Zeros and the Fundamental Theorem of Algebra (i) 4x3 − 6x2 − 8x + 15 = (k) (l) (m) (n) (o) (p) (q) (r) 3 2 4x2 − 12x + 10 = 31 31 +i x− −i 22 22 3 31 Zeros: x = − , x = ± i 2 22 x4 + x3 + 7x2 + 9x − 18 = (x + 2)(x − 1) x2 + 9 = (x + 2)(x − 1)(x + 3i)(x − 3i) Zeros: x = −2, 1, ±3i √ √ 3 1 x− x − −2 + 2 2 x − −2 − 2 2 6x4 +17x3 − 55x2 +16x +12 = 6 x + 3 2 √ 1 3 Zeros: x = − , x = , x = −2 ± 2 2 3 2 x5 − x4 + 7x3 − 7x2 + 12x − 12 = (x − 1) x2 + 3 x2 + 4 √ √ 3)( = (x − 1)(x − i √ x + i 3)(x − 2i)(x + 2i) Zeros: x = 1, ± 3i, ±2i √ √ 29 5 29 3 + 7x2 + 9x − 2 = (x + 2) x − − 5 + x x− − − 2...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online